Development of a generic framework for lumped parameter modeling - Yang Shuo; Amara Yacine; Hua Wei; Barakat Georges (Open Physics, 2020)
The purpose of this article is to present a generic reluctance network modeling tool dedicated to the modeling of electrical machines. This tool is used for the study of permanent magnet machines. The focus will be on the modeling methodology and software implementation. More precisely, the aspects related to genericity will be discussed. In order to validate the developed tool, the simulation of a 12 slot/10 pole flux-switching permanent magnet machine is conducted, and the results obtained from this generic framework are compared to the corresponding finite element analysis.